A Simple Protocol for Visualization of RNA-Protein Complexes by Atomic Force Microscopy - Tripepi, Andrea; Shakoor, Huma; Klapetek, Petr (Current protocols, 2025)
Atomic force microscopy (AFM) has recently received increasing interest in molecular biology. This technique allows quick and reliable detection of biomolecules. However, studying RNA-protein complexes using AFM poses significant challenges. Here, we describe a simple and reliable method to visualize positively charged proteins bound to RNA that does not require metallic cations. This method allowed us to effectively detect and visualize Staufen-RNA complexes by height or logarithmic stiffness. The study of the mechanical properties is particularly important in the case of protein-coated RNA complexes, where RNA cannot be detected by height channel. In any case, it is necessary to compare AFM data with the data derived from other techniques like nuclear magnetic resonance, X-ray crystallography, cryogenic electron microscopy, and small-angle X-ray scattering. © 2025 The Author(s). Current Protocols published by Wiley Periodicals LLC. Basic Protocol: Preparation and visualization of RNA-protein complex.
Keywords: RNA; AFM; Microscopy, Atomic Force; mikroskopie atomárních sil; proteiny vázající RNA; RNA-Binding Proteins; RNA–protein complex formation; Staufen